Distribution of Antibiotic-Resistant Enterobacteriaceae Pathogens in Potable Spring Water of Eastern Indian Himalayas: Emphasis on Virulence Gene and Antibiotic Resistance Genes in Escherichia coli - Singh, Ashish Kumar; Das, Saurav; Kumar, Santosh; Gajamer, Varsha Rani; Najar, Ishfaq Nabi; Lepcha, Yangchen D.; Tiwari, Hare Krishna; Singh, Samer (Frontiers in Microbiology, 2020)
Every year millions of people die due to fatal waterborne diseases around the world especially in developing countries like India. Sikkim, a northeastern state of India, greatly depends on natural water sources. About 80% of the population of Sikkim depends on natural spring water for domestic as well as agricultural use. Recent waterborne disease outbreaks in the state raises a concering question on water quality. In this study, we analyzed water quality especially for the detection of Enterobacteriaceae from four districts of the state. Isolation with selective culture media techniques and taxonomic characterization of Enterobacteriaceae bacteria with 16S rRNA gene showed the prevalence of Escherichia coli (37.50%), Escherichia fergusonii (29.41%), Klebsiella oxytoca (36.93%), Citrobacter freundii (37.92%), Citrobacter amalonaticus (43.82%), Enterobacter sp. (43.82%), Morganella morganii (43.82%), Hafnia alvei (32.42%), Hafnia paralvei (38.74%), and Shigella flexneri (30.47%) in the spring water of Sikkim. Antibiotic susceptibility test (AST) showed resistance of the isolates to common antibiotics like ampicillin, amoxicillin as well as to third generation antibiotics like ceftazidime and carbapenem. None of the isolates showed resistance to chloramphenicol. E. coli isolated from spring water of Sikkim showed presence of different virulence genes such as stx1 (81.81%), elt (86.66%), and eae (66.66%) along with resistance gene for ampicillin (CITM) (80%), quinolones (qnrB) (44.44%), tetracycline (tetO) (66.66%), and streptomycin (aadA1) (66.66%). The data indicates a high incidence rate of multiple antibiotic resistant enteric bacteria in the spring water of Sikkim. Additionally, the presence of enteric bacteria in the water samples indicates widespread fecal contamination of the spring water.